The Role of Trees in Sand Dune Rehabilitation: Insights from Global Experiences - Lucian Dinca; Aurora Coca; Nicu Constantin Tudose; Mirabela Marin; Gabriel Murariu; Dan Munteanu (Applied Sciences)
The present review summarizes the existing knowledge regarding the afforestation of sand dunes. Our main focus was on the role of trees in stabilizing and rehabilitating these complex ecosystems. We analyzed 937 publications through a systematic bibliometric review and then proceeded to select 422 articles that met our criteria. This methodological approach—combining a comprehensive bibliometric analysis with an in-depth traditional literature review—represents a novel contribution to the field and allows for both quantitative trends and qualitative insights to be captured. This was then complemented by an in-depth literature review. Our results sustain the global importance of this subject, as they include studies from more than 80 countries, with a focus on the USA, China, Australia, and Japan. We have also identified a series of main tree species that are usually used in the afforestation of sand dunes (Pinus, Acacia, Juniperus) and then proceeded to analyze their ecologic and socio-economic impact. As such, we have analyzed case studies from all continents, showcasing a variety of strategies that were successful and adapted to local conditions. This did not exclude challenges, mainly invasive species, low survival rates, and effects on biodiversity and stabilization. The main factors that impact the success of afforestation are represented by topography, soil structure, water dynamics, and climate. Unlike previous reviews, this study offers a global synthesis of both the scientific output and the applied outcomes of sand dune afforestation, bridging the gap between research and practice. As such, afforestation has a positive impact on soil fertility and carbon sequestration but can also present a major risk to native ecosystems. In this context, the present review highlights the need to adopt strategies that are unique for that site, and that must integrate all aspects (ecological, social, economic) to ensure good results. Our ISI-indexed literature review helped us to address the link between the current knowledge, research trends, and future topics that must be addressed.